The effect of using e-learning technology in learning the skill of clean and jerk in students of Physical Education and Sports Sciences - Shaker, Ali Sadiq; Tuama, Hussein Mhaibes; Radhi, Mahmoud Nasser (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The purpose of this paper was to identify the effect of using the e-learning technology method and the method used by the teacher in teaching clean and jerk skill to students of the College of Physical Education and Sports Sciences of the University of Kufa, as well as to identify the difference in the effect between using these two methods in teaching clean and jerk skill for students. In terms of research methodology, the researchers used the experimental method. A total of 40 students of the first stage participated in the study and were equally assigned into two equal groups (control and experimental). The control group (the method used by the teacher) included 20 students and the experimental group (e-learning technology method) included also 20 students. A statistically significant difference was found in both groups (control and experimental) in student’s performance level with clean and jerk skill in post test results (p<0.05), compared to pre-test. Also, there were statistically significant differences (p<0.05) in the second post-test between the experimental group (M=7.34, SD=8.4) and the control group (M=5.55, SD=0.49), in student’s performance level with clean and jerk skill. The researchers reached several conclusions, including the development in the performance level of students with clean and jerk skill for both groups (control and experimental), as well as the differences in the effect of e-learning method and the method used by the teacher in developing the level of student’s performance with clean and jerk skill, in favor of the experimental group (e-learning).